2022
DOI: 10.3390/metabo12100956
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Ameliorates Ulcerative Colitis in Mice by Modulating the Gut Microbiota and Metabolites

Abstract: Ulcerative colitis (UC) is a chronic recurrent inflammatory disease of the gastrointestinal tract. Recent studies demonstrate that the phenolic tannin paeonol (Pae) attenuates UC in mouse models by downregulating inflammatory factors. However, its molecular mechanism for UC treatment has not been explored from the perspective of the gut microbiota and metabolomics. In this study, we investigated the effects of Pae on colonic inflammation, intestinal microbiota and fecal metabolites in 3% dextran sodium sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…We screened the top 10 phyla and genera in terms of abundance and presented them on bar charts. Firmicutes and Bacteroidetes accounted for the largest proportion of phyla at the phylum level, which is consistent with previous studies (Liu, Zhou, et al, 2022; Zheng et al, 2022). And in the CTRL group, Firmicutes and Campylobacterota were more abundant at the phylum level (Figure 8a).…”
Section: Resultssupporting
confidence: 92%
“…We screened the top 10 phyla and genera in terms of abundance and presented them on bar charts. Firmicutes and Bacteroidetes accounted for the largest proportion of phyla at the phylum level, which is consistent with previous studies (Liu, Zhou, et al, 2022; Zheng et al, 2022). And in the CTRL group, Firmicutes and Campylobacterota were more abundant at the phylum level (Figure 8a).…”
Section: Resultssupporting
confidence: 92%
“…The gut microbiota is well-known to play an essential role in improving the UC phenotypes. , For this reason, we evaluated the efficacy of NEPs versus EPs and DFs in improving body weight, DAI, colon length, spleen weight, and cecal weight of the tested UC mice (Figure A). It was found that the body weight and the colonic length of DSS-treated mice were significantly reduced when compared to NC mice (Figure B–D, p < 0.05), and this reduction was obviously restrained by consumption of NEPs ( p < 0.05), but the colitis mice supplemented with EPs or DFs did not exhibit this change.…”
Section: Resultsmentioning
confidence: 99%
“…Ileibacterium and Alloprevotella, a group of bacteria associated with SCFA formation, have been proved to modulate systemic inflammation. , The gut microbiome, known as the human second genome, has been proved to be closely related to the occurrence and development of UC . Many studies also indicated that the patients or mice with UC exhibited a significant disruption of intestinal microorganisms. ,, For these reasons, we evaluated whether NEPs could ameliorate gut microbiota disturbance to relieve UC symptoms, and a chronic colitis model was established by drinking 1.5% DSS water in C57/B6J mice. The UC symptoms and colonic damage are approved to be highly similar between the patients and mice, , while supplementation of NEPs could significantly improve these symptoms, which was followed by DFs, and this similar effect could not be achieved by EP treatment, indicating that NEPs improved the DSS-induced UC symptoms by regulating the structure of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…animalis F1–7 reduced Turicibacter and Clostridium_sensu_stricto_1 . The abundance of Romboutsia was abnormally increased in the intestines of inflamed mice . F1–7 intervention reduced the abundance of Romboutsia , implying the weakening of the inflammatory response.…”
Section: Discussionmentioning
confidence: 95%